Correction: Novel findings with reassessment of exome data: implications for validation testing and interpretation of genomic data. (November 2018) - Gibson, Kristin McDonald; Nesbitt, Addie; Cao, Kajia; Yu, Zhenming; Denenberg, Elizabeth; DeChene, Elizabeth; Guan, Qiaoning; Bhoj, Elizabeth; Zhou, Xiangdong; Zhang, Bo; Wu, Chao; Dubbs, Holly; et al.
In the published version of this article, the name of the 18th author was misspelled as Minjie Lou. The correct name is Minjie Luo. The authors regret the error.